The longest ride [videorecording (DVD)] - Eastwood, Scott, 1986-; Robertson, Brittany; Huston, Jack, 1982-; Chaplin, Oona, 1986-; Alda, Alan, 1936-; Davidovich, Lolita; Sparks, Nicholas (20th Century Fox Home Entertainment, 2015)
The star-crossed love affair between Luke, a former champion bull rider looking to make a comeback, and Sophia, a college student who is about to embark upon her dream job in New York City's art world. As conflicting paths and ideals test their relationship, Sophia and Luke make an unexpected and fateful connection with Ira, whose memories of his own decades-long romance with his beloved wife deeply inspire the young couple.